2013
DOI: 10.5430/ijfr.v4n2p115
|View full text |Cite
|
Sign up to set email alerts
|

Role of Financial Development in Economic Growth: Evidence from Savings and Credits Cooperative Societies in Tanzania

Abstract: In this paper we examine the role of Savings and Credits Cooperative Societies (SACCoS) in the economic growth of Tanzania by answering two main questions. First, are financial services in SACCoS significant factors for economic growth? Second, are financial services in SACCoS Granger causing economic growth? We use credits-real GDP per capita ratio and savings-real GDP per capita ratio as proxy measures for financial services and real GDP per capita for economic growth. We employ Newey-West standard errors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The result is in accord with previous study by Subhashree, (2013) indicates that a large and rapid increase in income tends to raise the rate of household savings because household capacity to save increases with household income. This result is also consistent with the other empirical studies by Horioka and Wan,(2007), Qin and Ndiege, (2013). The interest rate was also found positive and significant in determining household saving at 1 %.…”
Section: Factors Influence Household Savingsupporting
confidence: 92%
“…The result is in accord with previous study by Subhashree, (2013) indicates that a large and rapid increase in income tends to raise the rate of household savings because household capacity to save increases with household income. This result is also consistent with the other empirical studies by Horioka and Wan,(2007), Qin and Ndiege, (2013). The interest rate was also found positive and significant in determining household saving at 1 %.…”
Section: Factors Influence Household Savingsupporting
confidence: 92%
“…We present test results as in line with Qin et al (2013) in Table 3. In order to achieve better presentation of results we refrain from tabulating equations where due to data availability no test results could be yielded.…”
Section: Resultsmentioning
confidence: 99%
“…We then run Granger causality tests (Hassan et al, 2011;Nwakanma et al, 2014;Qin & Ndiege, 2013) as the multivariate time series diagnostic approach for determining whether past values of one variable are useful for predicting another one. In particular, based on the VAR models we test whether, after controlling for past y, past z can forecast y t .…”
Section: Methodsmentioning
confidence: 99%
“…Hence SACCOS have solved the problem of capital inadequacy for rural people in Tanzania. Qin and Ndiege (2013) and Bwana and Mwakujonga (2013) revealed that SACCOS significantly contribute to GDP of Tanzania. The government of Tanzania promotes the establishment of SACCOS even to very remote areas because of their importance contribution to the country economy (Wangwe, 2004).…”
Section: Background Of the Studymentioning
confidence: 99%